2003
DOI: 10.1074/jbc.m307572200
|View full text |Cite
|
Sign up to set email alerts
|

Active Nitric Oxide Produced in the Red Cell under Hypoxic Conditions by Deoxyhemoglobin-mediated Nitrite Reduction

Abstract: Recent studies have generated a great deal of interest in a possible role for red blood cells in the transport of nitric oxide (NO) to the microcirculation and the vascular effect of this nitric oxide in facilitating the flow of blood through the microcirculation. Many questions have, however, been raised regarding such a mechanism. We have instead identified a completely new mechanism to explain the role of red cells in the delivery of NO to the microcirculation. This new mechanism results in the production o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
333
2
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 321 publications
(348 citation statements)
references
References 37 publications
9
333
2
2
Order By: Relevance
“…1). Subsequent work examining the kinetics and product distribution of this reaction under a range of conditions (12,25,33) has continued to employ nitrite concentrations and [NaNO 2 ]͞ [deoxy-heme] ratios well above physiological values. A clue to the importance of reactant concentrations on this chemistry emerged from EPR studies, which revealed, in the aftermath of mixing very high concentrations of nitrite and deoxyHb, essentially equal subunit populations of nitrosyl heme [␣Fe(II)NO Ϸ ␤Fe(II)NO], whereas spectra obtained under conditions that simulate key aspects of the in vivo situation exhibit substantial ␤Fe(II)NO preference (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Subsequent work examining the kinetics and product distribution of this reaction under a range of conditions (12,25,33) has continued to employ nitrite concentrations and [NaNO 2 ]͞ [deoxy-heme] ratios well above physiological values. A clue to the importance of reactant concentrations on this chemistry emerged from EPR studies, which revealed, in the aftermath of mixing very high concentrations of nitrite and deoxyHb, essentially equal subunit populations of nitrosyl heme [␣Fe(II)NO Ϸ ␤Fe(II)NO], whereas spectra obtained under conditions that simulate key aspects of the in vivo situation exhibit substantial ␤Fe(II)NO preference (16).…”
Section: Discussionmentioning
confidence: 99%
“…However, our kinetic analysis (12), like other work on nitrite͞Hb interactions (25)(26)(27), was performed at supraphysiological nitrite͞Hb ratios (typically nitrite:Hb 1:10-10:1 vs. Ϸ1:1,000 in vivo), with a global spectral deconvolution approach that was not adapted to recognize ''minority species.'' We now examine the product distribution of reactions of nitrite and deoxyhemoglobin by using a modified approach in which spectral deconvolution is used to test for the presence of minority species formed at physiologically relevant concentrations, whereas studies of the chemical reactivity of these species are used to verify their identity.…”
mentioning
confidence: 99%
“…For headspace NO analysis, culture headspace was anaerobically sampled and injected into the purge cell of a 280i NO analyzer (Sievers). For solution NO, samples of culture solution were injected into a purge solution in anoxic vials (31). The headspace from these vials was injected into the NO analyzer.…”
Section: Methodsmentioning
confidence: 99%
“…High-capacity NO production in eukaryotic systems has two dominant but not unique routes: 1) the primary production via enzymatic oxygenation of the guanidine group of L-arginine to form NO and L-citrulline by a specific enzyme, NO synthase (NOS) [17]; and 2) the secondary production by enzymatic reduction of nitrite [18,19] via nitrite reductase activity (NRA) of xanthine oxidase [20,21], mitochondrial cytochrome complexes [22,23], deoxyhemoglobin [24][25][26], and some NOS isozymes under anoxic conditions [27]. It is generally assumed that the primary NO synthesis from L-arginine oxidation by NOS and following retrograde diffusion of the gaseous messenger is responsible for focal "neurotransmitter-like" actions of NO [28], as well as for pathogen-induced escalation of cytotoxic defense [29].…”
Section: No Productionmentioning
confidence: 99%